FROM THE HISTORY OF THE ESTABLISHMENT OF AMIR TEMUR'S RELATIONS WITH EUROPEAN COUNTRIES (Modern education and development, 2024)
This article highlights the importance of relations between Amir Temur and Bayazid for European countries. Amir Temur's invasion of the Middle East and Asia Minor attracted the attention of European countries. It was this attention that later led to the establishment of relations between Amir Temur and European countries.